The intra‐oral application of a skin regeneration system in the rehabilitation of post‐operative cancer patients with tongue tethering: a technical note. (7th August 2017) - Farrier, J.; Beech, A.
Abstract: Post‐operative healing following oral cancer resection and reconstruction can lead to distortion of oral anatomy, interruption of function and extensive scar contraction. We present what is to our knowledge the first reported and successful use of a one stage dermal regeneration template system (Integra ®, Integra Life Sciences Corp, Plainsboro, NJ, USA) to assist in the oral rehabilitation of a group of oral cancer patients.